A CRITICAL DISCOURSE ANALYSIS OF GENDER REPRESENTATIONS IN EFL TEXTBOOK OF SENIOR HIGH SCHOOL - Andini, Tresna Nur; Hidayat, Didin Nuruddin; Husna, Nida; Alek, Alek (English Education Department, 2023)
This present study investigates gender representation in an EFL textbook in Senior High Schools by using multimodal critical discourse analysis. The data is collected from the unit contents of the English Textbook by Kementerian Pendidikan dan Kebudayaan Republik Indonesia 2017, which is used for senior high school and vocational high school. The study uses qualitative with Fairclough's three-dimensional framework to analyze the data collected. The focus variables include the frequency of gender representation and women's and men's social and domestic roles. The finding revealed that the EFL textbook was biased, imbalanced, and unequal for the position of male and female; for the frequency of gender representation in pictorial, males dominated around 25.6%, and females were only 11.6%. Then for gender representation in the passage text, the male was dominated by 46.3% and female was 34.3%. Next, for gender representation in conversation text, the male-dominated was 51.8%, and the female was 38.8%. The last one is gender representation in exercise text, the male-dominated by 31.33%, and the female was 40.97%. For the category of gender's social and domestic role, it revealed that males tend to do a social role associated with higher education and knowledge. At the same time, female is related to the traditional view in society that is associated with social status and hype only. Therefore, the result showed that the gender representation in this textbook was not represented equally.